1996
DOI: 10.1590/s0037-86821996000300006
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da eficácia e tolerância do artesunato oral isolado e em associação com mefloquina, no tratamento da malária falciparum não complicada em área endêmica do Pará, Brasil

Abstract: With the objective to evaluate the efficacy and tolerance of artesunate in the treatment of noncomplicated falciparum malaria in endemic area of the State of Pará, 153 patients were randomized and studied in three groups, distributed by therapeutical scheme (I received mefloquine 1000 mg, II used artesunate 600 mg followed by mefloquine 500 mg). Evaluation was made by daily clinical and parasitological examination, in the first 7 days, and weekly until the 35th day of the follow-up. Biochemical and hematologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…6 Although in vitro resistance to MQ has been reported from this area since the early 1980s, 7 only recently have a small number of well-documented cases of RI in vivo resistance to a single dose of 15 mg/kg been recorded. 8,9 In this trial in the Peruvian Amazon region, we found no evidence of resistance to either MQ or MQ-AS; however, at the time the …”
Section: Discussionmentioning
confidence: 54%
“…6 Although in vitro resistance to MQ has been reported from this area since the early 1980s, 7 only recently have a small number of well-documented cases of RI in vivo resistance to a single dose of 15 mg/kg been recorded. 8,9 In this trial in the Peruvian Amazon region, we found no evidence of resistance to either MQ or MQ-AS; however, at the time the …”
Section: Discussionmentioning
confidence: 54%
“…After the completion of our work (1996-1997), Cardoso et al [7] published a study of subjects from the Amazon region who had been treated with similar mg/kg doses of mefloquine during 1993-1994, in which they also found a 100% cure rate, although they examined a lower number of fields per thick smear.…”
Section: Discussionmentioning
confidence: 98%
“…The credibility of such programs depends on a high mefloquine efficacy. Although there seem to be no published reports of widespread mefloquine resistance in Brazil [5][6][7], periodic clinical trials should be conducted to monitor its efficacy, especially because of the possibility of mefloquine cross-resistance with quinine [8]. When we initiated this study, there had been no reported clinical studies of mefloquine in Brazil for over a decade, during which time mefloquine resistance rose dramatically in Southeast Asia [9].…”
mentioning
confidence: 99%
“…In vitro resistance to MQ has been reported for several years from the Brazilian Amazon region, 14 but its clinical significance has been ques-tioned since only recently have well-documented cases of in vivo resistance (RI) to 15 mg/kg MQ been recorded. 15,16 MQ resistance has not been reported from other countries in the region. If MQ-resistant strains do occur in Peru, they probably would be found in the Amazon region and might easily be missed in a trial with only 14-day follow-up.…”
Section: Discussionmentioning
confidence: 91%